Cost-Effectiveness: An Evolving Science - CARROLL, JOHN (BioCommunications LLC, 2008)
Overseas, government payers challenge biopharma companies to show evidence of cost-effectivess. Collaboration there could provide a model for U.S. payers and manufacturers.